Respuesta :
Answer:
1 solution
Step-by-step explanation:
-5 - 11r = 6 ( -2r - 3 )
Distribute:
-5 - 11r = -12r - 18
Add 18 to both sides:
13 - 11r = -12r
Add -11r to both sides:
13 = -r
Divide each side by -1:
-13 = r
1 is your answer
Hope this helps!
-5 + (-11r) = -12r - 18
By adding 5 to both sides you remove -5 on the left side and end up with:
-11r = -12r -13
By adding 12r to both sides you get rid of the -12r on the right side and get:
1r = -13
This is the same as:
r = -13
So this would only be 1 solution.
By adding 5 to both sides you remove -5 on the left side and end up with:
-11r = -12r -13
By adding 12r to both sides you get rid of the -12r on the right side and get:
1r = -13
This is the same as:
r = -13
So this would only be 1 solution.